Rigorous P-matrix for uniform NSPUDT - DANICKI, E. (Archives of Acoustics, 1992)
A rigorous scattering matrix in mixed representation (P-Matrix) is presented for natural single-phase unidirectional transducer (NSPUDT) of surface acoustic wave (SAW). It results from spectral theory of propagation of SAW in periodic system of elastic metal strips on arbitrary anisotropic piezoelectrics.